Please solve this question
![\sec^{4} q \: - \sec {}^{2} q \: = \tan ^{4} q \: + \tan ^{2} q \: \sec^{4} q \: - \sec {}^{2} q \: = \tan ^{4} q \: + \tan ^{2} q \:](https://tex.z-dn.net/?f=+%5Csec%5E%7B4%7D+q+%5C%3A++-++%5Csec+%7B%7D%5E%7B2%7D+q+%5C%3A+++%3D+%5Ctan+%5E%7B4%7D+q+%5C%3A++%2B++%5Ctan+%5E%7B2%7D+q+%5C%3A+)
Answers
Answered by
3
Answer:
see the attachment
Step-by-step explanation:
hope its helpful for you
Attachments:
![](https://hi-static.z-dn.net/files/d31/0f038aff22e281ec826de51506172552.jpg)
Answered by
1
LHS:sec 4 θ−sec 2 θ=sec 2 θ(sec 2 θ−1)=(1+tan 2 θ)tan 2 θ=tan 2 θ+tan 4 θHence LHS = RHS.
Similar questions